Program Peningkatan Kualitas Baca Tulis Al – Qur’an Anak Usia Dini Di TPQ Sabilil Huda - Devi Rohmatus Sa’adah; Rohmad Muzakki (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
The Qur'an education and teaching institution is an islamic educational and teaching institution outside the school or can also be referred to as non-formal education for children and aims to educate santri and santriwati (children) in order to be able to read the Qur'an properly and correctly in accordance with tajwid science as the main target. In this report entitled "The Role of The Qur'an Education Park in Improving the Quality of Early Childhood Writing in TPQ Sabilil Huda". This report discusses the community's assistance about how important the existence and role of the Qur'an Education Park in improving the quality of reading and writing the Qur'an, especially for early childhood. The type of method used in this report is the Participatory Action Research (PAR) method which is research that actively involves all parties who are willing (stakeholders) in reviewing ongoing actions (in the name of their own experience as a problem) in order to make changes and improvements in a better direction. The aim is to assist the community to know the role of the Qur'an Education Park in improving the quality and reading skills of early childhood in TPQ Sabilil Huda and to know the methods and obstacles faced by the Education Garden of the Qur'an Sabilil Huda. The results of the activities of the PKM Research Program of the author found that the role of TPQ Sabilil Huda is very large in creating a generation of Muslims who obey worship and noble religion and its existence has a very large role for the community of Dsn. Buka'an Ds. Keling especially parents in shaping their children into a generation of Qur'an who from an early age have known their religion through the Qur'an by learning to read the Qur'an.